2014
DOI: 10.1038/cddis.2014.503
|View full text |Cite
|
Sign up to set email alerts
|

Blocking autophagy enhanced cytotoxicity induced by recombinant human arginase in triple-negative breast cancer cells

Abstract: Depletion of arginine by recombinant human arginase (rhArg) has proven to be an effective cancer therapeutic approach for a variety of malignant tumors. Triple-negative breast cancers (TNBCs) lack of specific therapeutic targets, resulting in poor prognosis and limited therapeutic efficacy. To explore new therapeutic approaches for TNBC we studied the cytotoxicity of rhArg in five TNBC cells. We found that rhArg could inhibit cell growth in these five TNBC cells. Intriguingly, accumulation of autophagosomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 38 publications
1
51
1
Order By: Relevance
“…31 Meanwhile, rhArg has been demonstrated to be significant cytotoxicity in triple-negative breast cancers and laryngeal squamous cell carcinoma. 9, 10 However, it has never been reported whether NSCLC cells were sensitive to rhArg treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Meanwhile, rhArg has been demonstrated to be significant cytotoxicity in triple-negative breast cancers and laryngeal squamous cell carcinoma. 9, 10 However, it has never been reported whether NSCLC cells were sensitive to rhArg treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been widely reported that depleting amino acids could stimulate autophagy, in response to nutrition stress. 12 Mounts of studies indicated that autophagy played a cytoprotective role in pathogenesis process and antitumor therapy.…”
mentioning
confidence: 99%
“…Our results suggest that peiminine induces G1/G0 phase arrest by increasing the expression of p21 and p27 and decreasing the expression of cyclin D1, CDK2 and CDK4. Autophagy is a double-edged sword in tumour progression and treatment: it can either facilitate cancer survival under metabolic stress or induce autophagic tumour cell death [35,36]. Mounting evidence accumulated in recent years suggests that inhibition of autophagy can reduce the treatment resistance of chemotherapy and radiotherapy in various types of cancers [37,38], which is also the case in GBM treatment [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…143 Inhibition of autophagy in amino acid deficient conditions induces tumor cell death, mainly because of further exacerbation of energy dearth. 167,168 Also, longer persistence of autophagy is proposed to eventually lead the activation of caspase-dependent cell death pathways, as autophagy and apoptotic cell death pathways are interconnected and also share some common pathways through the induction of the membrane permeability transitions. 169171 Induction of apoptotic pathways is another consequence of arginine depletion and anti-tumor mechanism of arginase I-mediated arginine deprivation.…”
Section: Arginasementioning
confidence: 99%